Elucidation of the Molecular Interaction between miRNAs and the Gene, Involved in Acute Myeloid Leukemia, by the Assistance of Argonaute Protein through a Computational Approach - Rohit Pritam Das; V. Badireenath Konkimalla; Surya Narayan Rath; Jagadish Hansa; Manaswini Jagdeb (Genomics & Informatics)
Acute myeloid leukemia is a well characterized blood cancer in which the unnatural growth of immature white blood cell takes place, where several genes transcription is regulated by the micro RNAs (miRNAs). Argonaute (AGO) protein is a protein family that binds to the miRNAs and mRNA complex where a strong binding affinity is crucial for its RNA silencing function. By understanding pattern recognition between the miRNAs-mRNA complex and its binding affinity with AGO protein, one can decipher the regulation of a particular gene and develop suitable siRNA for the same in disease condition. In the current work, HOXA9 gene has been selected from literature, whose deregulation is well-established in acute myeloid leukemia. Four miRNAs (mir-145, mir-126, let-7a, and mir-196b) have been selected to target mRNA of HOXA9 (NCBI accession No. NM_152739.3). The binding interaction between mRNAs and mRNA of HOXA9 gene was studied computationally. From result, it was observed mir-145 has highest affinity for HOXA9 gene. Furthermore, the interaction between miRNAs-mRNA duplex of all chosen miRNAs are docked with AGO protein (PDB ID: 3F73, chain A) to study their interaction at molecular level through an in silico approach. The residual interaction and hydrogen bonding are inspected in Discovery Studio 3.5 suites. The current investigation throws light on understanding of AGO-assisted miRNA based gene silencing mechanism in HOXA9 gene associated in acute myeloid leukemia computationally.